A revision of the lysianassid genus Waldeckia with the description of four new species (Crustacea, Amphipoda, Lysianassidae, Waldeckiinae subfam. nov.) - Lowry, J. K.; Kilgallen, N. M. (Zootaxa, 2014)
Waldeckia Chevreux is a genus of scavenging lysianassoid amphipods with distribution records from Antarctica, Australia, Thailand, Indonesia, Singapore, the Philippines, Vietnam, China and Japan. The genus is revised and diagnosed against all other genera of the Lysianassidae and the subfamily Waldeckiinae is established. All known species are redescribed and a key is provided. Three new species of Waldeckia (W. dempseyae sp. nov., W. tangaroa sp. nov., W. warreen sp. nov.) are described from Australian waters, and one (W. selayarensis sp. nov.) from Indonesia and Australia. Waldeckia crenulata Pirlot, 1936, from the Philippines and Indonesia, is described in detail for the first time. Waldeckia chevreuxi Stebbing, 1910 is placed in the synonymy of W. nitens, and W. elephas is placed in the synonymy of W. nudum. Orchomene orchospina Hirayama, 1986 and O. tomiokaensis Hirayama, 1986 are transferred to Waldeckia. Waldeckia scrupulosa Mateus & Mateus, 1986 cannot be placed in a genus based on the original description. This revision brings the number of species in the genus to 14.